Comparative metabolomic analysis of spaghetti meat and wooden breast in broiler chickens: unveiling similarities and dissimilarities - Choi, Janghan; Shakeri, Majid; Kim, Woo Kyun; Kong, Byungwhi; Bowker, Brian; Zhuang, Hong (Frontiers in Physiology, 2024)
Introduction Spaghetti meat (SM) and wooden breast (WB) are emerging myopathies in the breast meat of fast-growing broiler chickens. The purpose of the study was to investigate the metabolomic differences between normal (N), SM, and WB fillets 24 h postmortem. Materials and methods Eight chicken breasts for each experimental group were collected from a commercial processing plant. Supernatant from tissue homogenates were subjected to ultra-performance liquid chromatographytandem mass spectrometry (UPLC-MS) analysis. Results and methods A total of 3,090 metabolites were identified in the chicken breast meat. The comparison of WB and N showed 850 differential metabolites (P < 0.05), and the comparison of SM and N displayed 617 differential metabolites. The comparison of WB and SM showed 568 differential metabolites. The principal component analysis (PCA) plots showed a distinct separation between SM and N and between WB and N except for one sample, but SM and WB were not distinctly separated. Compared to N, 15-Hydroxyeicosatetraenoic acid (15-HETE) increased, and D-inositol-4-phosphate decreased in both SM and WB, indicating that cellular homeostasis and lipid metabolism can be affected in SM and WB. The abundance of nicotinamide adenine dinucleotide (NAD) + hydrogen (H) (NADH) was exclusively decreased between SM and N (P < 0.05). Purine metabolism was upregulated in SM and WB compared to N with a greater degree of upregulation in WB than SM. Folic acid levels decreased in SM and WB compared to N (P < 0.05). Steroid hormone biosynthesis was downregulated in SM compared to N (P < 0.05). Carbon metabolism was downregulated in SM and WB compared to N with greater degree of downregulation in WB than SM (P < 0.05). These data suggest both shared and unique metabolic alterations in SM and WB, indicating commonalities and differences in their underlying etiologies and meat quality traits. Dietary supplementation of deficient nutrients, such as NADH, folic acids, etc. and modulation of altered pathways in SM and WB would be strategies to reduce the incidence and severity of SM and WB.